Oscillation Criteria of First Order Neutral Delay Differential Equations with Variable Coefficients - Fatima N. Ahmed; Rokiah Rozita Ahmad; Ummul Khair Salma Din; Mohd Salmi Md Noorani (Abstract and Applied Analysis)
Some new oscillation criteria are given for first order neutral delay differential equations with variable coefficients. Our results generalize and extend some of the well-known results in the literature. Some examples are considered to illustrate the main results.